A qualitative exploration of the participants' experience of a web-based physiotherapy program for people with multiple sclerosis: Does it impact on the ability to increase and sustain engagement in physical activity?. Issue 21 (8th October 2020) - Dennett, Rachel; Coulter, Elaine; Paul, Lorna; Freeman, Jennifer
Abstract: Background: Web-based exercise and physical activity interventions are being developed as a potential way to help people with multiple sclerosis achieve and maintain increased physical activity levels. Seeking feedback from people who have used such interventions will help guide the development process. Methods: In-depth interviews were used to explore the experiences of participants who used a web-based physiotherapy intervention as part of a feasibility randomized controlled trial. Interviews were audio-recorded, transcribed verbatim and analyzed using thematic analysis. Results: Eleven people (age 28–68) were interviewed. Most perceived that their physical activity had increased, primarily due to completing twice-weekly web-based physiotherapy sessions. Three key themes were identified. 'It's all in one place' encompasses the value of having a convenient and portable program. 'Keeping an eye' captures people's thoughts regarding the supervision offered by the physiotherapist, through the website, and 'Hopes and expectations' reflects the importance of having opportunity to discuss what may be gained from using such a program. Conclusions: This intervention offered a convenient, flexible and portable physiotherapy program which most people perceived helped them achieve and sustain increased levels of physical activity. Talking with people about expectations is important, particularly if a person's condition is deteriorating. IMPLICATIONS FOR REHABILITATION: When discussing the potential benefits of exercise programs with people with multiple sclerosis it is important to have honest and open conversations about the expectations of what may be achieved. This is particularly important for people with progressive disease. Web-based interventions may be most valuable to people who are technology literate, seek flexibility regarding where and when to exercise, prefer to exercise independently and have the confidence and skills to self-manage. Trial registration: ClinicalTrials.gov identifier: NCT02508961.